Widespread hybridization in the introduced hog deer population of Victoria, Australia, and its implications for conservation. Issue 18 (4th September 2019) - Hill, Erin; Linacre, Adrian; Toop, Simon; Murphy, Nicholas; Strugnell, Jan
Abstract: In Australia, many species have been introduced that have since undergone drastic declines in their native range. One species of note is the hog deer ( Axis porcinus ) which was introduced in the 1860s to Victoria, Australia, and has since become endangered in its native range throughout South‐East Asia. There is increased interest in using non‐native populations as a source for genetic rescue; however, considerations need to be made of the genetic suitability of the non‐native population. Three mitochondrial markers and two nuclear markers were sequenced to assess the genetic variation of the Victorian population of hog deer, which identified that the Victorian population has hybrid origins with the closely related chital ( Axis axis ), a species that is no longer present in the wild in Victoria. In addition, the mitochondrial D‐loop region within the Victorian hog deer is monomorphic, demonstrating that mitochondrial genetic diversity is very low within this population. This study is the first to report of long‐term persistence of hog deer and chital hybrids in a wild setting, and the continual survival of this population suggests that hybrids of these two species are fertile. Despite the newly discovered hybrid status in Victorian hog deer, this population may still be beneficial for future translocations within the native range. However, more in‐depth analysis of genetic diversity within the Victorian hog deer population and investigation of hybridization rates within the native range are necessary before translocations are attempted. Abstract : The hog deer ( Axis porcinus ) was introduced in the 1860s to Victoria, Australia, and has since become endangered in its native range throughout South‐East Asia. There is some belief that this population could be a source for genetic rescue within the native range, so three mitochondrial and two nuclear markers were sequenced to identify which species of hog deer was introduced and to assess the genetic variation of the Victorian population. It was discovered that this population has hybrid origins with the closely related chital ( Axis axis ) and comprises low genetic diversity at the D‐loop region. Although this population is comprised of hybrids, it may still be beneficial for the genetic rescue of native hog deer; however, more research into the hybridization rates in the native range is now needed.